Issues of Structuring the Procedural Support in the Audit Practice - Lubenchenko О. Е.; Redko О. Yu. (Statistics of Ukraine, 2024)
The updated Law of Ukraine “Audit of Financing Reporting and Audit Activities in Ukraine” has enforced amendments in the implementation of supervision over the audit activities and brought the domestic audit practice into line with European requirements. The financial reporting of business entities in all the material aspects has to conform with the requirements of national provisions (standards) of accounting, International Financial Reporting Standards or other established requirements. The financial reporting audit as an audit service is aimed at the expression of an independent auditor’s opinion with respect of such reporting. This can be achieved through implementing specific audit procedures. The article contains a definition of the procedure. The procedure is interpreted as an interconnected or officially established sequence (or order, or algorithm) of any kind of actions or any kind of activity. International Standards for Quality Control, Auditing, Review, Other Assurance, and Related Services, edition 2020 (ISA) provide a nomenclature of procedures for each of the standards. However, the authors demonstrate that the audit practice requires a structuring of the procedures by audit phase: preparatory, planning, fieldwork, completion. Audit procedures for these phases are outlined on the basis of ISA analysis. The preparatory phase requires procedures such as assessment, enquiry, management, supervision and review of the performed work. The authors highlight that the procedures of management, supervision and review of the performed work are specific to all the phases of audit. The phase of planning requires risk assessment, with its procedural support consisting of enquiry, observation and inspection, analytical procedures for risk assessment. Also, this phase involves planning of further audit procedures for collecting evidence on financing reporting in response to the assessed risks. The fieldwork phase requires using tests of control actions and materiality procedures (tests of details and analytical materiality procedures). According to ISA, the latter ones cover: inspection, observation, external confirmation, recurrent calculation (recalculation), recurrent fulfilment / testing of control actions, analytical procedures, including the use of a forecasting model. The completion phase involves assessment of audit evidence (accumulation of misstatements detected in time of audit, assessing the impact of uncorrected misstatements on the financing reporting), submission of enquiries to management staff of a business entity which reporting is subject to audit, correction of the materiality level (in case of need). The structuring of procedures by phase allows practical auditors to collect sufficient and acceptable evidence that is supposed to lay the ground for an auditor’s opinion on the financial reporting.